Evaluation of video traffic behavior metrics in an experimental multicast network - Facchini, Higinio Alberto; Pérez, Santiago Cristobal; Dantiacq, Alejandro; Hidalgo, Fabian (Enfoque UTE, 2020)
Currently, there is a significant change in data traffic on networks, both local and Internet, across the spectrum of possible customers, whether fixed or mobile. The consumption of video traffic increases day by day in all its formats. Service providers are required more bandwidth, quality and performance, for all products, but mainly those based on video. This article presents an improved version of our laboratory tests for generic networks with four sub-scenarios, which allow injecting multicast video traffic, represented in different codecs. The topology of network used includes a streaming server and up to 20 desktop computers as clients. The most important metrics to be analyzed have been defined, based on performance and quality of service (QoS) measurements under limited bandwidth conditions. Experimental numerical results can be useful for administrators, simulation analysts, designers, and data network planners. But, also, this document aims to serve as a guide for the management of similar networks and the efficiently use available resources, without compromising performance and QoS.